2008
DOI: 10.2174/157340608784872299
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Protects the Brain Against the Oxidative Imbalance Promoted by Type 2 Diabetes

Abstract: We aimed to investigate whether metformin protects the brain against the oxidative imbalance promoted by type 2 diabetes. This study analyzed the effect of metformin on oxidative stress markers (thiobarbituric acid reactive substances (TBARS), malondialdehyde (MDA) and carbonyl groups), hydrogen peroxide (H(2)O(2)) levels, non-enzymatic antioxidant defenses [reduced (GSH) and oxidized (GSSG) glutathione and vitamin E] and enzymatic antioxidant defenses [glutathione peroxidase (GPx), glutathione reductase (GRed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 0 publications
7
48
0
Order By: Relevance
“…This concern needs to be addressed by direct testing of the drug in animal models, in conjunction with learning, memory and behavioral tests. Although the precise mechanism of action of metformin in the CNS remains largely unknown, recent studies (39,40), together with ours, suggest that metformin crosses the blood brain barrier and exerts specific pharmacological effects in rodent brains upon chronic administration. Indeed, our study using a comparable dose (2 mg/mL is equivalent to a clinical dosage of 300 mg/kg/ day) indicates that systemically administrated metformin for 6 days increases brain AMPK activation and BACE1 protein levels (Fig.…”
Section: Figmentioning
confidence: 63%
“…This concern needs to be addressed by direct testing of the drug in animal models, in conjunction with learning, memory and behavioral tests. Although the precise mechanism of action of metformin in the CNS remains largely unknown, recent studies (39,40), together with ours, suggest that metformin crosses the blood brain barrier and exerts specific pharmacological effects in rodent brains upon chronic administration. Indeed, our study using a comparable dose (2 mg/mL is equivalent to a clinical dosage of 300 mg/kg/ day) indicates that systemically administrated metformin for 6 days increases brain AMPK activation and BACE1 protein levels (Fig.…”
Section: Figmentioning
confidence: 63%
“…In some models, antioxidative activity of metformin has been associated with its hypoglycemic effect, but in the presented study HFD-fed rats did not exhibit hyperglycemia. Numerous studies have demonstrated that both T1D (Type 1 diabetes) and T2D are associated with decreased activity and expression of antioxidant enzymes and that metformin treatment can restore normal conditions (13,19,62). In our experimental design, HFD-fed rats exhibited augmented markers of oxidative stress (lipoperoxides) accompanied by a significant decrease of liver GSH content and SOD activity and elevated catalase activity.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that AICAR exerts a protective effect against apoptosis in astrocytes induced by fatty acids [30] and by glucose deprivation in hippocampal neurons [31]. In addition, metformin treatment significantly decreases oxidative stress levels and increases the levels of anti-oxidants such as glutathione and Mn-superoxide dismutase in the brain [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, metformin has anti-oxidative effects in diabetic brain [14] and neuroprotective effects induced by permeability transition pore opening [15].…”
Section: Introductionmentioning
confidence: 99%